Tafsir Era Millenial: Kajian Atas Penafsiran KH.Sya’roni Ahmadi di Channel Youtube Official Menara Kudus - Azizah, Laili Noor; Khoirona, Muhammad Dilla (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2020)
This article discusses interpretations in the millennial era especially in Kudus, such as the study of the interpretation of K.H. Sya’roni Ahmadi which makes the Official YouTube Channel of Menara Kudus as the medium. In the YouTube content the Menara Kudus Official Channel carries the study of commentasries K.H. Sya’roni Ahmadi by utilizing the current development. Studies that are well understood in all circles are not only limited to the conceptual and contextual, but rather combining the two that make an advantage of the study of interpretation K.H. Sya’roni Ahmadi. He uses the deriction of the qibla in the interpretation on the YouTube Channel with various steps which are certainly different from the presentation of other commentary studies. To analyze, the writer needs to use a descriptive qualitative approach in gathering existing information and knowing the sosio-historical approach in terms of the study interpretation, through sociologi theory from study that can uncover society’s problems and oral tradition theory in the delivery of interpretive studies.